Geomorphology and Sedimentology of a Rapidly Retreating Alpine Glacier: Insights From the Taschachferner, Tirol, Austria - D. P. Le Heron; P. Mejías Osorio; M. Heninger; B. J. Davies (Earth Science, Systems and Society)
The rapid retreat and fragmentation of Alpine glaciers is widely reported as humanity faces dramatic climate change in mountainous regions. This rapid change leads to changes in sedimentary processes, which are exposed in recently deglaciated regions. These Alpine glacier forefields offer a wide spectrum of settings through which the ancient sedimentary record can be interpreted. Glacial valley orientation, slope inclination and lithology, and plumbing of subglacial and englacial meltwater drainage all influence the immediate preservation potential of glacial sediments upon deposition. In this contribution, we explore the geomorphology and sedimentology of the Taschachferner (a valley glacier), presenting a new geological-geomorphological map. This small glacier drains an icefield in the Ötztal Alps, and its current ice margin lies at approximately 2550 m a.s.l. Thus far, the glacial sedimentology and its bedrock geology have not been subject to investigation. The bedrock geology is dominated by E-W striking units of paragneiss and amphibolite, and the latter exhibit a series of well-preserved striations together with meltwater-sculpted bedforms (p-forms). The lower region of the glacier can be divided into two parts: (i) a clean-ice part, on the northern valley side with a low, subdued profile and (ii) a debris-covered part at the southern valley side, covered with supraglacial debris. The valley margins are dominated by several generations of lateral moraines, the most prominent of which corresponds to the 1852 Little Ice Age Maximum. A well-developed “hanging sandur” is observed immediately in front of the ice margin. This consists of a series of sand and gravel bars cradled in the lee of an interpreted regional fault cross-cutting the bedrock. Sandur deposition is currently influenced and overprinted by dead ice, influencing the trajectory and location of river channels and gravel bars. This paper provides clear lessons regarding the distribution of ice-margin facies associations, which must be incorporated into models of glacier decay in the context of a rapidly warming climate.